2016
DOI: 10.1111/asj.12559
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein induces mitochondrial biogenesis and decreases reactive oxygen species generation in cultured avian muscle cells, possibly via an up‐regulation of peroxisome proliferator‐activated receptor γ coactivator‐1α

Abstract: It has been shown that oleuropein, a phenolic compound in the fruit and leaves of the olive tree (Olea europaea) induces mammalian uncoupling protein 1 (UCP1) expression via an increased secretion of noradrenaline and adrenaline. This study investigated the effects of oleuropein on avian UCP (avUCP) expression as well as genes related to mitochondrial oxidative phosphorylation and biogenesis in cultured avian muscle cells, together with reactive oxygen species generation. Oleuropein induced avUCP as well as pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…It is realistic to speculate that physiologically plausible picomolar concentrations of OLE as tested in this study, may be sufficient to activate adaptive responses and favor protein homeostasis by activating complex yet intriguing vitagene pathways [66,67]. Interestingly, recent data report that OLE can induce mitochodrial biogenesis as well as activate the cellular anti-oxidant defense system in avian muscle cells [68]; thus sustaining its potential beneficial effects in neurodegenerative disease where the balance between oxidant and anti-oxidant systems is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…It is realistic to speculate that physiologically plausible picomolar concentrations of OLE as tested in this study, may be sufficient to activate adaptive responses and favor protein homeostasis by activating complex yet intriguing vitagene pathways [66,67]. Interestingly, recent data report that OLE can induce mitochodrial biogenesis as well as activate the cellular anti-oxidant defense system in avian muscle cells [68]; thus sustaining its potential beneficial effects in neurodegenerative disease where the balance between oxidant and anti-oxidant systems is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hydroxytyrosol was previously shown to improve mitochondrial respiration and reduce oxidative stress in the brain of db/db mice via AMPK activation [ 85 ]. Tyrosol and oleuropein were reported to decrease oxidative damage in cultured cells [ 86 , 87 ] and in a rat model of myocardial ischemia, by upregulating the expression of SIRT-1 and its nuclear translocation [ 88 ]. A recent study also reported that daily extra-virgin olive oil (EVOO) intake for six months improved synaptic integrity, with lower insoluble protein aggregation, via autophagy activation, in a rat model of Alzheimer’s disease [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the treatment with hydroxytyrosol (HT) increases creatine kinase activity and myosin heavy chain expression, which are indicators of muscle cell differentiation and contraction strength, respectively [48,49]. Moreover, oleuropein derivatives reduced the tumor necrosis factor-α (TNF-α)-induced downregulation of mitochondrial biogenesis, increasing the peroxisome proliferator-activated receptor-gamma coactivator (PGC-1α), mitochondrial complexes (I and II) and myogenin expression [50]. These data indicated that oleuropein improves the mitochondrial development and function in muscle cells under inflammatory stress.…”
Section: Discussionmentioning
confidence: 99%